2003
DOI: 10.1590/s0036-36342003000900009
|View full text |Cite
|
Sign up to set email alerts
|

Cervical carcinogenesis: the role of co-factors and generation of reactive oxygen species

Abstract: ResumenDiversos co-factores de riesgo han sido asociados consistentemente con displasia cervical y cáncer invasor. Es necesario un mayor número de investigaciones que utilicen diseños de cohorte prospectivos para describir el proceso de carcinogénesis y el mecanismo biológico de cada uno de estos factores. Adicionalmente, futuras investigaciones serán necesarias para definir el papel de los anticonceptivos hormonales en la promoción de la carcinogénesis cervical. Mientras que muchas preguntas científicas inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It seems that the deficiency of certain antioxidants might influence the course of the infection [ 99 ]. Antioxidants modulate the expression of genes associated with the transcriptional AP-1 complex [ 100 ], and in turn, ROS lead to activation of AP-1, a factor involved in the expression of E6 and E7 oncoproteins [ 101 ].…”
Section: The Link Between Inflammation Oxidative Stress and Hpv-mentioning
confidence: 99%
“…It seems that the deficiency of certain antioxidants might influence the course of the infection [ 99 ]. Antioxidants modulate the expression of genes associated with the transcriptional AP-1 complex [ 100 ], and in turn, ROS lead to activation of AP-1, a factor involved in the expression of E6 and E7 oncoproteins [ 101 ].…”
Section: The Link Between Inflammation Oxidative Stress and Hpv-mentioning
confidence: 99%
“…, carotenoids and tocopherols), inflammation and smoking have been associated with the progression of HPV infection to cervical dysplasia 3–6. It has been proposed that increased production of reactive oxygen species (ROS) may be the common mechanism through which these cofactors influence the natural history of HPV infections 4, 7. A few prospective studies have demonstrated an association between the contributors of ROS ( e.g.…”
mentioning
confidence: 99%
“…Interestingly the lower SOD in circulation reported in cervical cancer [46] may have a role in downregulation of the serum calcineurin activity. There is clearly strong evidence on the involvement of reactive oxygen species (ROS) in cervical cancer [47] and it can most likely alter the calcineurin activity atleast in the tissues without affecting its expression. This argument is also supported by an observation that activity of creatine kinase B, a ROS sensitive protein, is downregulated in cervical cancer [48].…”
Section: Discussionmentioning
confidence: 99%